Investigating the relationship between corporate tax avoidance and corporate culture in large South African companies - Van Der Spuy, Pieter van Aardt (Department of Finance and Tax, 2022)
Not all companies are equally aggressive in their pursuit of corporate tax avoidance, which explains intensive research on the determinants of tax avoidance. Many determinants have been investigated, but the process of tax avoidance, and the relationships between corporate tax avoidance, longtermism (indicative of a stakeholder-orientated corporate culture), and CEO characteristics (informed by upper-echelon theory), are not yet fully understood. Much of previous research is conceptualised from theories such as principal-agent theory. This study investigates the influence of stakeholder orientation, using corporate culture, on corporate tax avoidance, in response to calls for more research using stakeholder theory. A mixed-method approach is used. The quantitative stream uses regressions to investigate the relationship between corporate tax avoidance, corporate culture, and tax-knowledgeable CEOs, based on a sample of 112 large, listed South African companies, studied over a period of 15 years. The South African setting allows the operationalisation of a tax-knowledgeable CEO, based the homogenous nature of CEOs' qualifications in South Africa, where many are chartered accountants. The results suggest that long-term oriented companies pay more tax on average. The results further suggest that tax knowledgeable CEOs are associated with more tax avoidance. The qualitative stream conducts eleven interviews with corporate tax advisors, showing the influence of corporate culture and CEO characteristics on corporate tax avoidance processes, but also how corporate culture and CEO-characteristics mutually inform each other. Altogether, the evidence indicates that the effect of corporate culture is less static than expected, and that the influence of corporate culture on tax avoidance can transcend the influence of CEO-characteristics, as an upperechelon effect. The interviews suggest mechanisms used by CEOs to influence tax culture, such as the creation of a company-wide awareness of the strategic importance of low effective tax rates. These results also indicate the ethical dilemma faced by executives of large companies when considering the use of tax-deductible corporate social responsibility initiatives, not to benefit shareholders or agents, but rather to benefit society as a corporate stakeholder, when governments would not.